x[a-b+ab/a-b)=y[a+b-ab/a+b]
x+y=2a2
solve it using elimination method.

please don't send links and send a picture if possible.

Dear student
xa-b+aba-b-ya+b-aba+b=0    ...(1)x+y=2a2    ..(2)Multiply eq(2) by a-b+aba-b,we getxa-b+aba-b+ya-b+aba-b=2a2a-b+aba-b    ...(3)Subtract (3) from (1), we getxa-b+aba-b-ya+b-aba+b-xa-b+aba-b-ya-b+aba-b=-2a2a-b+aba-bya+b-aba+b+a-b+aba-b=2a2a-b+aba-bya-ba+b-ab+(a+b)(a-b+ab)a+ba-b=2a2a-b+aba-bya2+ab-a2b-ab-b2+ab2+a2-ab+a2b+ab-b2+ab2a-ba+b==2a2a-b+aba-by2a2-2b2+2ab2a-ba+b==2a2a-b+aba-bya2-b2+ab2=a2a-b+aba+by=a2a2-ab+a2b+ab-b2+ab2a2-b2+ab2y=a2a2-b2+a2b+ab2a2-b2+ab2Put the value of y in (2), we getx+a2a2-b2+a2b+ab2a2-b2+ab2=2a2x=2a2-a2a2-b2+a2b+ab2a2-b2+ab2x=2a4-2a2b2+2a3b2-a4+a2b2-a4b-a3b2a2-b2+ab2x=a4-a2b2+a3b2-a4ba2-b2+ab2x=a2a2-b2+ab2-a4ba2-b2+ab2x=a2-a4ba2-b2+ab2
Regards

  • -1
What are you looking for?